Au‐Decorated ZnO Nanorod Powder and Its Application in Photodegradation of Organic Pollutants in the Visible Region. Issue 9 (8th March 2021) - Yao, Chujun; Lin, Jiamin; Li, Lequn; Jiang, Kai; Hu, Zhigao; Xu, Ning; Sun, Jian; Wu, Jiada
Abstract : A simple, green, and cost‐effective approach to synthesizing powdered Au‐decorated ZnO (ZnO–Au) nanorods having high photocatalytic activity by growing ZnO nanorods and decorating the grown ZnO nanorods with Au nanoparticles via hydrothermal reactions is reported. The morphology and structure of the synthesized samples are characterized by field‐emission scanning electron microscopy, transmission electron microscopy, selected‐area electron diffraction, X‐ray diffraction and Raman backscattering measurements. The optical properties are examined through optical absorbance and photoluminescence measurements. The ZnO nanorods have a hexagonal wurtzite structure, whereas the Au nanoparticles are uniformly distributed on the surfaces of the ZnO nanorods and present a face‐centered cubic structure. Compared with bare ZnO nanorods, the synthesized ZnO–Au nanorods exhibit a significant increase in ultraviolet and visible light absorption and noticeable quenching of PL, revealing efficient generation of electron–hole pairs by light excitation in a wide spectral region and effective suppression of recombination of photogenerated electrons and holes. In addition to the enhanced photocatalytic activity in the ultraviolet region, the ZnO–Au nanorods are expected to have a high visible photocatalytic activity and good stability as visible photocatalysts, which are demonstrated by the photodegradation of organic Rhodamine B and methylene blue dyes under visible light illumination. Abstract : Au‐decorated ZnO nanorod powders are prepared by growing ZnO nanorods and decorating the grown ZnO nanorods with Au nanoparticles via hydrothermal reactions. The prepared ZnO–Au nanorod powders have a high photocatalytic activity in the ultraviolet and visible region and good stability as photocatalysts and are used to efficiently photodegrade organic pollutants under sunlight irradiation.